A writer's guide to ancient Rome - Fleiner, Carey, 1965- (Manchester University Press, 2020)
A writer's guide to Ancient Rome serves as a guide and inspiration to the Roman population, economy, laws, leisure and religion for that author, student or general reader who is seeking an introduction to what made the Romans tick. The Guide considers trends and themes from roughly 200 B.C. to A.D. 200 with the occasional foray into the antecedents and legacy on either side of the period. Each chapter explicates its main themes with examples from the original sources. Throughout are suggestions for resources to mine for the subject at hand and particular topics affected by scholarly debate and changing interpretation based on new discoveries or re-interpretation of written and material remains.